1979
DOI: 10.2307/3280312
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic Make-Up of Trypanosoma cruzi Culture Forms: Identification of a Specific Component

Abstract: A comparison of Trypanosoma cruzi water soluble antigens with those of stercorarian and salivarian trypanosomes, and Leishmania using immunoprecipitation in gels and immunoelectrophoresis, with the aid of hyperimmune rabbit serum and heterologous adsorptions showed the following. 1) There is a high complexity of soluble antigens of T. cruzi and T. rangeli. 2) At the intraspecific level our results demonstrated the antigenic stability of T. cruzi when maintained in vitro, and that there was quantitative antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 11 publications
1
24
0
Order By: Relevance
“…This crossed reaction has been shown by immunoelectrophoresis, ELISA, indirect immunofluorescence, immunoblotting, double immunodiffusion (Afchain et al 1979, Antony et al 1979, Guhl & Marinkelle 1982, Grogl & Kuhn 1984, Basso et al 1989, O' Daly et al 1994, Saldaña & Sousa 1996. These studies have generally shown that the 2 parasite species share at least 60% of their antigens.…”
Section: Antigenic Characterizationmentioning
confidence: 94%
“…This crossed reaction has been shown by immunoelectrophoresis, ELISA, indirect immunofluorescence, immunoblotting, double immunodiffusion (Afchain et al 1979, Antony et al 1979, Guhl & Marinkelle 1982, Grogl & Kuhn 1984, Basso et al 1989, O' Daly et al 1994, Saldaña & Sousa 1996. These studies have generally shown that the 2 parasite species share at least 60% of their antigens.…”
Section: Antigenic Characterizationmentioning
confidence: 94%
“…More studies must be performed to better understand the T. rangeli antigenic variation among strains isolated from different geographical regions, since T. rangeli and T. cruzi share 60% of their soluble antigenic coat (Afchain et al 1979).…”
Section: Resultsmentioning
confidence: 99%
“…Both parasites have similar geographical distributions and share the same host range and often have identical insect vectors. Although considered non-pathogenic to man [1], T. rangeli is of medical interest as a possible source of confusion in the serological diagnosis of Chagas' disease due to its well-known immunological cross-reactivity with T. cruzi [2][3][4][5]. In experimental infection of mice, several exposures to T. rangeli cause an increase in antibody titres to T. cruzi and it is possible that these antibodies modulate the outcome of active T. cruzi infection [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%